2022
DOI: 10.11646/zootaxa.5197.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of Indian Pyraloidea (Lepidoptera)

Abstract: We catalogue 1,695 Indian Pyraloidea species in 509 genera. Of these, Pyralidae comprises 518 species in 182 genera, which represents 8.35% of the global Pyralidae diversity of 6,197 species. Crambidae are represented by 1,177 species in 327 genera, accounting for 11.29% of the global Crambidae diversity of 10,418 species. Botys medullalis Snellen, distributed in Indonesia, is reinstated to species status as Sciorista medullalis (Snellen), stat. rev., comb. nov. Sylepta [sic] picalis Hampson, 1903, syn. nov. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Hymenoptera were photographed for identification and identification done by using (Broad, 2011;Forshage & Nordlander, 2008;Sheth et al, 2020)also Lepidoptera, Odonata also photographed and identified by using (Nandy & Babu, 2012;Rao et al, 2013;Singh et al, 2022).…”
Section: Insectmentioning
confidence: 99%
“…Hymenoptera were photographed for identification and identification done by using (Broad, 2011;Forshage & Nordlander, 2008;Sheth et al, 2020)also Lepidoptera, Odonata also photographed and identified by using (Nandy & Babu, 2012;Rao et al, 2013;Singh et al, 2022).…”
Section: Insectmentioning
confidence: 99%
“…described a new species, L. monticola from Nepal. Later, Wang et al (2017 described five new species of Lista from China: L. angustusa , L. gilvasa Wang, Chen & Wu, 2017, L. longifundamena Wang, Chen & Wu, 2017, L. menghaiensis Wang, Chen & Wu, 2017and L. sichuanensis Wang, Chen & Wu, 2017 (Rong et al 2021, Nuss et al 2003-2022, with four species from India (Singh et al 2022). In the present study two additional species, Lista monticola and Lista furciillatusa are reported for the first time from India (Fig A).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rong et al (2021) reviewed the genus Lista from China and described five new species: L. furcellata Li & Rong, 2021, L. serrata Li & Rong, 2021, L. strumiformis Li & Rong, 2021, L. yunnanensis Li & Rong, 2021 and L. zhengi Li & Rong, 2021. At present, the genus is known by 20 species distributed in the Oriental, Australasian and Palaearctic regions (Rong et al 2021, Nuss et al 2003–2022), with four species from India (Singh et al 2022). In the present study two additional species, Lista monticola and Lista furciillatusa are reported for the first time from India (Fig A).…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, a number of authors from India and across the globe have occasionally reported and described many new species and new records from the superfamily Pyraloidea (Rao & Sivaperuman, 2021;Singh et al 2020;Mathew, 2006;Raha et al 2017;Murthy et al 2015). A catalogue of Indian Pyraloidea was published recently, and it included 1,695 described species of Pyraloidea moths distributed among 509 genera (Singh et al 2022). The family Pyralidae has a total of 518 species distributed over 182 genera; of these, 171 species spread across 47 genera are assigned to the subfamily Pyralinae in India.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the genus Pyralis comprises of 17 species reported across the country with no species records from Jammu and Kashmir. In the Indian subcontinent, the region of Northeast India is home to the greatest variety of Pyralinae, followed by the West and Northwest Himalayas, and then the Central Himalayas (Singh et al 2022).…”
Section: Introductionmentioning
confidence: 99%